Budget Policy Innovation Through Participatory Budgeting In The Provincial Government Of Banten - Maulana, Delly (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
The involvement of civil society and society groups through the concept of participatory budgeting in public management, especially in the budgeting process is a key factor in realizing good governance. In the context of the Provincial Government of Banten, this province is an area with a good budget potential, both from the original revenue of the region and from the overall income, but the condition has not made a significant impact on the development of the region, as it can be seen from the two districts in Banten Province which are included in the category of underdeveloped areas, namely Lebak District and Pandeglang District.This condition clearly requires innovation in budget planning by putting forward several principles, namely: prioritizing accountability, paying attention to value for money, creating transparency, using honesty approach in financial management, and encouraging the creation of control in budgeting implementation.Therefore, this paper tries to give an idea of the importance of budget policy innovation in Provincial Government of Banten through participatory budgeting, so that high budget potential can give significant impact to the development and prosperity of the society in Banten Province.